Application of Mycorrhizal Biofertilizer and NPK Fertilizer to the Growth and Yield of Edamame Soybean Plants - Yohanes Parlindungan Situmeang; Desak Ketut Tristiana Sukmadewi; Ni Putu Agnis Candrawati (Agriwar Journal, 2024)
This study aims to evaluate the effect of doses of arbuscular mycorrhizal biofertilizer and NPK fertilizer and their interaction in increasing the growth and yield of edamame soybean plants. This research was carried out in Kutuh Village, South Kuta District, Badung Regency, Bali in March-June 2023. This study used a Factorial Group Randomized Design (2 factors) which was repeated 3 times. The first factor is the application of mycorrhizal biofertilizer (M) which consists of 4 levels (0; 7.5; 15; dan 22.5 g plant-1). The second factor is the application of NPK chemical fertilizer which consists of 4 levels (0; 1.25; 2.5; dan 3.75 g plant-1). Arbuscular mycorrhizal biofertilizer treatment of 22.5 g plant-1 (M3) gave the highest yield of fresh seed weight of 22.92 g plant-1 with an increase of 34.19% compared to without mycorrhizal fertilizer treatment (M0) which was 17.08 g plant-1. The treatment dose of NPK fertilizer 3.75 g plant-1 (N3) resulted in the highest fresh weight of seeds of 25.75 g plant-1 or an increase of 101.96% compared to treatment without NPK fertilizer which was 12.75 g plant-1. The interaction between mycorrhizal biofertilizer 15 g plant-1 and NPK fertilizer 3.75 g plant-1 resulted in the highest average number of leaves of 18.57 strands. Meanwhile, the interaction without biofertilizer treatment with NPK fertilizer 3.75 g plant-1 resulted in the highest average number of branches, namely 5.73 pieces.